Feline Niemann-Pick disease type C - therapeutic studies and genetic characterization - Somers, Kyra Lynn, author; Thrall, Mary Anna, advisor; Akkina, Ramesh, committee member; Bowen, R. A., committee member; Brown, Diane E., committee member; Schultheiss, Patricia, committee member (Colorado State University. Libraries, 2000)
Niemann-Pick Disease Type C (NPC) is an autosomal recessive neurovisceral storage disorder in which defective intracellular transport of cholesterol results in lysosomal lipid accumulation. Clinical manifestations are heterogeneous, but usually include neonatal jaundice, onset and progression of neurological signs, hepatosplenomegaly, neurovisceral storage and premature death. The lysosomal storage in NPC involves a complex lipidosis characterized by accumulation of unesterified cholesterol, phospholipids and sphingomyelin. A feline model of NPC has been characterized and is clinically, biochemically, and morphologically equivalent to the major form of human NPC, NPC1. Chapters one and two of this dissertation describe therapeutic trials conducted in the feline model of NPC, while chapters three and four focus on the genetic characterization of the feline model of NPC. Chapter one discusses the results of a diet study conducted in the feline model of NPC. The study goal of the cholesterol restricted diet was to lower the amount of low density lipoprotein (LDL) available to cells, hypothetically reducing subsequent lysosomal accumulation of unesterified cholesterol and other lipids. Results indicated liver lipid concentrations of unesterified cholesterol, cholesterol ester, and phospholipids in NPC affected treated kittens were similar to those seen in NPC affected untreated kittens. Ganglioside concentrations in the NPC affected treated kittens and NPC affected untreated kittens were also similar. Histologic findings in liver sections from NPC affected treated kittens showed a diffuse uniform microvacuolar pattern within hepatocytes and Kupffer cells, compared to a heterogeneous macro/micro vacuolar pattern and prominent nodular fibrosis in NPC affected untreated kittens. Similar differences in vacuolar patterns were seen in splenic macrophages. Neurological progression of disease was not altered and dietary cholesterol restriction did not significantly decrease storage in NPC affected treated kittens. Chapter two describes the findings of a drug study, in which a potent ganglioside synthesis inhibitor, N-butyldeoxynojirimycin (NB-DNJ) was evaluated as a potential therapy for NPC. The predominant storage material outside of the central nervous system (CNS) includes unesterified cholesterol, phospholipids and sphingomyelin. This is in contrast to the storage seen within the central nervous system, which is predominantly giycosphingolipids and in particular, gangliosides GM2 and GM3. A drug study was conducted to determine if NBDNJ would prevent and/or slow disease manifestation in this feline model of NPC. Preliminary results from this study were encouraging with evidence of decreased ganglioside storage within the CNS and delayed clinical disease progression. Chapter three summarizes complementation studies that were performed to determine if the gene responsible for the major form of human NPC and the feline model of NPC are orthologous. Cell fusions between human NPC and feline NPC fibroblasts were conducted to assess whether the multinucleated heterokaryons that were formed showed a reversal of the NPC phenotype. Cultured fibroblasts from NPC affected humans and NPC affected cats were hybridized and then analyzed for complementation by challenging the cells with LDL and subsequently staining with the fluorescent antibiotic filipin to visualize any abnormal accumulation of unesterified cholesterol. All of the multinucleated cells formed from the fusion of feline NPC fibroblasts and human NPC1 fibroblasts retained the NPC staining phenotype. This indicated an absence of complementation and suggested that the underlying defect in the major form of human NPC, NPC1, and this feline model of NPC involve orthologous genes. Chapter four describes the molecular genetic characterization of the feline model of NPC. Using human based PCR primers, initial fragments of the feline NPC1 cDNA were amplified and sequenced. Utilizing these sequences, feline specific PCR primers were generated and designed to amplify six bands which overlap and span the entire expected feline NPC1 open reading frame. Ninety-eight percent of the feline NPC1 cDNA has been sequenced and a single base substitution (G2870C) has been identified in all NPC affected cats evaluated. Additionally, known earners are heterozygous at the same allele. This mutation results in an amino acid change from cysteine to serine. The mutation site was utilized to design a PCR based assay for the identification feline NPC heterozygotes. Analysis to determine if cytogenetic abnormalities exist in NPC affected cats was performed. R-banded metaphase chromosome spreads of normal and known heterozygotes were generated. Karyotyping revealed that mutations resolvable at the cytogenetic level were not evident, supporting a small mutation. Utilizing FISH techniques, NPC1 PAC clones were used to determine the specific chromosomal location of NPC gene. Genetic characterization of feline NPC confirmed that the gene responsible for NPC in this feline model is the orthologous gene that is mutated in the major form of human NPC, further substantiating the value of this colony as an animal model for NPC1.
Keywords: zoology